2017
DOI: 10.1080/02705060.2017.1319429
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of morphological and functional variation among BluegillLepomis macrochiruspopulations across Grand Lake St Mary's watershed area

Abstract: A myriad of factors have been shown to influence the morphology of freshwater fish. However, studies that parse out where variation is coming from (e.g. body size, sex, and habitat) as well as what potential these changes have to influence function (e.g. swimming performance) are understudied. Therefore, the objectives of this study were to describe morphological variation of Bluegill Lepomis macrochirus across the Grand Lake St Mary's watershed area (northwest OH, USA) and test for covariation of morphology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Importantly, these observations provide additional links between morphology and swimming performance among both species, and are consistent with laboratory experiments on other taxa that have shown particular shapes (mainly related to fusiformity) to exhibit increased swimming performance (Qu et al 2013;Bell and Jacquemin 2017). In the field, morphological differences among individuals of the same or similar cyprinid species have been linked to specific macro and micro habitats (i.e., flow regime) and are often discussed in relation to swimming abilities or selection.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, these observations provide additional links between morphology and swimming performance among both species, and are consistent with laboratory experiments on other taxa that have shown particular shapes (mainly related to fusiformity) to exhibit increased swimming performance (Qu et al 2013;Bell and Jacquemin 2017). In the field, morphological differences among individuals of the same or similar cyprinid species have been linked to specific macro and micro habitats (i.e., flow regime) and are often discussed in relation to swimming abilities or selection.…”
Section: Discussionsupporting
confidence: 82%
“…The present study revealed that most body proportions of the three Lateolabrax species change with growth (Table 3). Although such proportional changes with growth have been reported for a number of fishes, including two black-and-white snappers of the genus Macolor (Kishimoto et al 1987), Spanish mackerel, Scomberomorusniphonius (Yokogawa 1996), giraffe catfish, Auchenoglanisoccidentalis (Chioma et al 2007), red porgy, Pagruspagrus (Minos et al 2008), bluegill, Lepomismacrochirus (Yokogawa 2013a; Bell and Jacquemin 2017), largemouth bass, Micropterussalmoides (Yokogawa 2014), two flatfishes of the genus Pleuronichthys (Yokogawa 2015), and some sea banjofishes of the genus Banjos (Matsunuma and Motomura 2017), such have been frequently neglected, particularly in taxonomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) demonstrated that all members of a school appear to benefit from the collective effort, so a stable group formation is associated with energetic savings for lead and trailing fish. The L. macrochirus population examined in this study have lived for many generations in a lentic environment, likely leading to adaptation to swimming in a relatively stable aquatic environment ( e.g ., Bell Jr. & Jacquemin, 2017). Still water conditions would make possible the laminar flow conditions that facilitate the energetic benefits of cohesive group swimming.…”
Section: Discussionmentioning
confidence: 99%